Modelled agroforestry outputs at field and farm scale to support biophysical and environmental assessments - Palma, J.H.N. (2017)
This report, comprising Deliverable 6.17, in the AGFORWARD project brings together examples of modelled outputs at field and farm scale to support the biophysical, social, and environmental assessment of the innovations selected from work-packages 2 to 5.